Use of Science Process Skills Indicators in "Avicom" Science Creativity Competition To Improve Student Critical Thinking - Acep Musliman*; Fitri Damayanti (Jurnal Pendidikan Sains Indonesia, 2023)
This research was conducted to determine the effectiveness of science process skills indicators (SPS) in scientific creativity competition activities as a learning approach in improving students' critical thinking skills. Avicom is a student scientific creativity competition organized by SMA Avicenna Cinere which is attended by junior high school students from various provinces in Indonesia. This study uses a qualitative descriptive method with a theoretical triangulation approach, namely observation, review, and analysis. The data comes from article documents, videos of participant activities, and competition activities. The results of the analysis of data sources show an increase in the ability of SPS participants in three basic skills which are shown in the form of scientific work products, scientific work articles, and scientific paper presentations. The results of the literature study, this SPS competency indicator has an impact on increasing the participants' critical thinking skills